What persists: embodying, performing, historiographing, changing (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This essay examined the play História (2026), by companhia brasileira de teatro, bringing the notions of repetition in reenactment and of acting historiography closer to the ethics of psychoanalysis, in order to discuss how the body, language, and trauma operate in the writing of personal, social, and theatrical history. Drawing on Jacques Lacan, Jacques-Alain Miller, Rebecca Schneider, and Daniele Ávila Small, it argued that the embodiment of memory exceeded the production of meaning and acted upon the traces that persist in the performing body, proposing an embodied historiography capable of challenging official narratives through operations of fragmentation, repetition, performative citation, and the opening of meaning.